PROKSEMIKA/SEMIOTIKA RUANG SEBAGAI SEBUAH PENDEKATAN UNTUK PENELITIAN DESAIN INTERIOR - Mr, Sumartono (Lintas Ruang: Jurnal Pengetahuan dan Perancangan Desain Interior, 2007)
Sometimes called a semiotics of space, proxemics becomesmore andmore popular as a researchmethod inmany academic surroundings. Proxemics is a study of how peoplemake a structure of microspace. Although this method is more popular among anthropologists, today it has been applied in other fields of study as well. A field of study which also benefits from this method is interior design. This is caused by the very fact that interior design deals a lot with microspaces. It is important to employ thismethod in interior design research in Indonesia.Keywords: interior design, proxemics, researchmethod, semiotics of space